2018
DOI: 10.1017/s0954422418000112
|View full text |Cite
|
Sign up to set email alerts
|

A review of select minerals influencing the haematopoietic process

Abstract: Micronutrients are indispensable for adequate metabolism, such as biochemical function and cell production. The production of blood cells is named haematopoiesis and this process is highly consuming due to the rapid turnover of the haematopoietic system and consequent demand for nutrients. It is well established that micronutrients are relevant to blood cell production, although some of the mechanisms of how micronutrients modulate haematopoiesis remain unknown. The aim of the present review is to summarise th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 145 publications
0
16
0
Order By: Relevance
“…Nevertheless, few studies investigated the role of intra- and extracellular Mg 2+ concentrations in megakaryocytes in the bone marrow. Mg 2+ deficiency may promote defects in platelet biogenesis due to changes in the cytoskeleton, promoting changes in platelet function [ 178 ]. In an experimental model, dietary Mg 2+ deficiency impaired megakaryocytes from bone marrow, resulting in a decrease in the number and larger shape than the cells of the control animals [ 56 ].…”
Section: The Role Of Mg 2+ In Hematopoiesismentioning
confidence: 99%
“…Nevertheless, few studies investigated the role of intra- and extracellular Mg 2+ concentrations in megakaryocytes in the bone marrow. Mg 2+ deficiency may promote defects in platelet biogenesis due to changes in the cytoskeleton, promoting changes in platelet function [ 178 ]. In an experimental model, dietary Mg 2+ deficiency impaired megakaryocytes from bone marrow, resulting in a decrease in the number and larger shape than the cells of the control animals [ 56 ].…”
Section: The Role Of Mg 2+ In Hematopoiesismentioning
confidence: 99%
“…While these bacteria might be vulnerable to ROS, they have the ability to scavenge H 2 O 2 , thus limiting hydroxyl production and surviving copper-induced stresses [21]. Correspondingly, mammalian tissue may suffer damage from excess copper exposure, while for copper deficient individuals, differentiation of blood cells may be hindered and patient health could suffer as a result [22]. For this reason, the World Health Organization has stated a copper limit of 2–3 mg/day [23].…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that, in rats or mice, an appropriate amount of zinc is needed for erythropoiesis. Although select minerals influencing the hematopoietic process have been reviewed recently [ 42 ], no direct animal studies have shown that zinc induces RBC formation in rats.…”
Section: Introductionmentioning
confidence: 99%